CroALa - Jovanović, Neven, filolog (Array, 2012)
Croatiae auctores Latini (CroALa), a text collection first published in 2009, makes freely accessible Latin texts written by or about people of Croatian origin from the Middle Ages to the twentieth century. The collection is intended primarily for scholars of Latin and neo-Latin literature and language and of Croatian history and culture. Texts are encoded in TEI XML and made searchable and readable online using PhiloLogic. This edition is intended to become a starting point and a useful tool for serious research, both traditional and digital. What can be done, besides adding more texts, to stimulate such research? This article describes the editors’ solutions in the following six areas: * fine-tuning the metadata and user interface to enable grouping of texts by author, period, genre, theme ; * providing language tools for users ; * adding supplemental material and links ; * making citations of CroALa texts easier and providing hyperlinks between texts ; * digitizing and providing access to finding aids for effective search and retrieval ; * disseminating the texts in outside repositories. These enhancements are realized by XML encoding, XSLT stylesheets, and configuring PhiloLogic. These solutions are simple to implement and are within reach of an advanced, non-programmer computer user. The documentation of these solutions serves a twofold pedagogical purpose: first, to help newcomers find their way around the immense potential enabled by the TEI encoding scheme and, second, to encourage other humanities scholars to become makers—or, at least, adapters—of TEI-based digital tools. Simply put, if I did it, you can do it too!